Rhinorrhea due to infusion of dexmecetomidine during rhinoplasty: A case report and current literature review - Uludağ Yanaral, Tümay; Karaaslan, Pelin; Güngör, Hande; Atalay, Yunus Oktay; Tobias, Joseph Drew (Galenos Publishing, 2022)
Dexmedetomidine can be used to achieve controlled hypotension during surgery. A 26-year-old female with no medical history underwent rhinoplasty. The maintenance of the anesthesia was achieved with propofol and dexmedetomidine (1 mcg kg-1 as a loading dose for 10 minutes, followed by 0.5 mcg kg-1 hr-1 as maintenance) infusion as total intravenous anesthesia. Propofol and dexmedetomidine infusion doses were adjusted to maintain a bispectral index of 40-60 and a mean arterial pressure of 55-65 mmHg. During surgery, rhinorrhea developed, which disrupted the view of the surgical field. An intravenous antihistamine and a topical decongestant were administered. However, rhinorrhea persisted, suggesting that it developed as a drug-related adverse effect. Dexmedetomidine was halted. Subsequently, the rhinorrhea decreased, and the quality of the surgical field improved. That was a temporary and reversible side effect, which resulted in no long-term sequela. To the best of our knowledge, this is the first patient who developed rhinorrhea as a side effect of dexmedetomidine infusion during rhinoplasty.
Keywords: Controlled Hypotension; Dexmedetomidine; Rhinoplasty; Rhinorrhea